2023
DOI: 10.18332/tpc/157598
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized controlled trial of automated and counselor-delivered text messages for e-cigarette cessation

Abstract: INTRODUCTION Automated text messaging programs show promise for e-cigarette cessation. Adding live text counseling could make them more engaging. We developed Quit the Vape (QTV), an automated e-cigarette cessation text messaging program, designed to be delivered as stand-alone or with counselor-delivered messages (QTV-C), and evaluated the acceptability and preliminary efficacy of QTV and QTV-C. METHODS Between May and August 2021, we recruited 58 e-cigarette users, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In young adults, an open-label pilot trial of nicotine replacement found potential vaping cessation efficacy, and text messaging was effective in a large trial . Promising data have come from pilot trials of other behavioral treatments …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In young adults, an open-label pilot trial of nicotine replacement found potential vaping cessation efficacy, and text messaging was effective in a large trial . Promising data have come from pilot trials of other behavioral treatments …”
Section: Discussionmentioning
confidence: 99%
“…7 Evidence from clinical trials to guide vaping cessation treatment, especially pharmacotherapy, is limited. [8][9][10][11][12][13] Varenicline demonstrated efficacy for e-cigarette cessation among adults in a randomized trial, 8 and a pilot trial suggested efficacy for nicotine replacement. 9 No medication has approval from the US Food and Drug Administration for vaping cessation.…”
mentioning
confidence: 99%
“…However, emerging research in the US is hampered by limited racial and ethnic diversity among participants. For example, a recently completed randomized controlled trial (RCT) with young adults (aged 18–24 years) demonstrated the effectiveness of the first vaping cessation intervention 6 . Limitations of the RCT included the small representation of Latinos (10.6%) – the largest minority group in the US 7 – and the exclusion of Spanish-speaking individuals 6 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recently completed randomized controlled trial (RCT) with young adults (aged 18–24 years) demonstrated the effectiveness of the first vaping cessation intervention 6 . Limitations of the RCT included the small representation of Latinos (10.6%) – the largest minority group in the US 7 – and the exclusion of Spanish-speaking individuals 6 . Given the substantial gap in vaping control research among Latinos, the purpose of the present study was thus two-fold: 1) assess the feasibility and cost of recruiting Latino young adults (aged 18–25 years) into a vaping cessation study via social media, and 2) describe the baseline characteristics of participants enrolled via social media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation